Pengaruh Beasiswa Kartu Indonesia Pintar Kuliah Terhadap Motivasi Belajar Mahasiswa Administrasi Publik - Wulandari, Agustina; Uceng, Andi; Hardianti, Hardianti; Sellang, Kamaruddin (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
The Smart Indonesia College Card (KIP-Kuliah) is real evidence that the government is working hard to ensure access to education for everyone, especially the underprivileged. The government's seriousness in realizing equal opportunities for education is also demonstrated through the Smart Indonesia College Card (KIP-Kuliah). Government support for higher education is an important step in improving the quality of human resources and encouraging social and economic progress. This study aims to determine the effect of the KIP-Kuliah scholarship on the learning motivation of public administration students in the 2020 and 2021 intakes at Muhammadiyah University of Sidenreng Rappang. The method used is a quantitative method with a sample size of 62 public administration students receiving the KIP-Kuliah. The sampling technique used is simple random sampling. Data were collected through observation, questionnaires and literature studies. Furthermore, it was analyzed using IBM SPSS Statistics 21.0. The results of the study showed that the KIP-Kuliah scholarship had a significant effect on the learning motivation of public administration students in the 2020 and 2021 intakes at Muhammadiyah University of Sidenreng Rappang with a value of 3.535. This finding provides theoretical contribution in the development of study of learning motivation, especially by emphasizing that financial support through KIP-Kuliah scholarship. From a practical perspective, the results of this study provide strategic input for policy makers of Muhammadiyah University of Sidenreng Rappang to continue to maintain and expand the scope of the KIP-Kuliah scholarship program.